Responsible Reading: Children's Literature and Social Justice - Alyson Simpson; Teresa Mary Cremin (MDPI AG, 2022)
In high accountability cultures, primary phase literacy education tends to focus on improving children's test scores. Driven by each country's performance in international league tables, this results in narrow, predominantly skills-based programmes designed to address attainment gaps. While scores may have been enhanced in recent years, there is little evidence that policy directives have positioned literacy in the lives of learners in ways that have become meaningful for them or been transferred into ways of thinking that promote social equity. Indeed, teaching practices that exacerbate the challenges for those young people who are already disadvantaged by circumstance have become more prevalent. Teachers, therefore, have an ethical responsibility to redress this through their teaching. This paper argues that literature is core to more equitable literacy development. As not all reading practices are equal, developing literacy education for a more socially just society needs to challenge the dominant pedagogic hegemony. Literature has the potential to spark the kind of mindful disruption necessary to shift standardised paradigms of thought, so literacy education should have children's literature at its heart. By examining the value of literature through a set of complementary lenses, this paper seeks to reveal its affordances in young people's lives. Then, through commentary taken from a pair of vignettes drawn from professional learning contexts, we illuminate shifts in teacher perception gained through scaffolded introduction to reading literary texts. The insights teachers gained reveal reconceptualisation of reading and the role of literature in primary education. This has the potential to redirect their future classroom practice. Consequently, we propose that for teachers to be adept at improving literacy outcomes through productive adoption and use of literary texts, they need: an aesthetic appreciation and knowledge of children's literature; personal experience with reading such literature as social practice; and pedagogic insight into how to use literature to teach literacy and develop volitional readers. We call this knowledge set the additive trio, noting that no 'step' or understanding is sufficient on its own, and that together they can enable the development of Reading Teachers who work with literature to advance the social justice agenda.